2000
DOI: 10.1029/2000jb900223
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation and diffusion creep of synthetic anorthite aggregates

Abstract: Abstract. Synthetic fine-grained anorthite aggregates were deformed at 300 MPa confining pressure in a Paterson-type gas deformation apparatus. Creep tests were performed at temperatures ranging from 1140 to 1480 K, stresses from 30 to 600 MPa, and strain rates between 2x 10 '6 and lx10 -3 s 'l. We prepared samples with water total contents of 0.004 wt % (dry) and 0.07 wt % (wet),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
277
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(303 citation statements)
references
References 84 publications
21
277
4
1
Order By: Relevance
“…Previously, Garrick-Bethell et al (2010) 16 (their Supporting Online Material Section 6) found that significant crustal flow was not likely to take place in less than 150 By. In those calculations, they used a creep flow law from Rybacki and Dresen (2000) 43 , with stress exponent n = 3 (indicating nonNewtonian dislocation creep), and an assumed basal temperature of 1175° C. However, in the present study, we calculated tidal heating cases with higher temperatures (Table S13). As described in the main text and Section S8.1, there are many uncertainties in the properties of the early crust, and while some temperatures we use may not be achieved, they illustrate the effect of progressively higher tidal heat fluxes on the shape parameters C 2,0 and C 2,2 .…”
Section: S82 -Lower Crustal Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Garrick-Bethell et al (2010) 16 (their Supporting Online Material Section 6) found that significant crustal flow was not likely to take place in less than 150 By. In those calculations, they used a creep flow law from Rybacki and Dresen (2000) 43 , with stress exponent n = 3 (indicating nonNewtonian dislocation creep), and an assumed basal temperature of 1175° C. However, in the present study, we calculated tidal heating cases with higher temperatures (Table S13). As described in the main text and Section S8.1, there are many uncertainties in the properties of the early crust, and while some temperatures we use may not be achieved, they illustrate the effect of progressively higher tidal heat fluxes on the shape parameters C 2,0 and C 2,2 .…”
Section: S82 -Lower Crustal Flowmentioning
confidence: 99%
“…Rybacki and Dresen (2000) 43 found that dry anorthosite likely flows via diffusion (Newtonian flow n = 0, m = 3) or dislocation creep (non-Newtonian, n = 3, m = 0), depending on σ and T. The driving stress for crustal flow is  Δρhg, where here Δρ is the crust-ocean density contrast, h is the thickness contrast, and g is gravity. For Δρ = 300 kg/m 3 and h = 10 km, σ  5 MPa.…”
Section: S82 -Lower Crustal Flowmentioning
confidence: 99%
“…Based on laboratory data (Rybacki and Dresen, 2000) that show a relatively strong rheology ("normal" models), we consider another two cases of lower crust viscosity with weaker rheology at the same temperature and stress. In the "weak" and "weakest" models, the parameter B n in the expression for dislocation creep (eq.…”
Section: Model Parametersmentioning
confidence: 99%
“…(1) Gleason and Tullis (1995) (2) Rybacki and Dresen (2000) (3) Hirth and Kohlstedt (1996) Source for diffusion and Peierls' creep laws in mantle: Kameyama et al (1999).…”
Section: Figure Captionsmentioning
confidence: 99%
“…Feldspar forms the major mineral constituent of rocks in the lower continental crust. Several experimental studies were recently conducted to examine the high-temperature rheology of fine-grained pure feldspar aggregates [Tullis and Yund, 1991;Tullis et al, 1996;Dimanov et al, 1998;Dimanov et al, 1999;Rybacki and Dresen, 2000;Rybacki et al, 2006]. These previous experiments were performed in triaxial compression at low axial strain < 30%.…”
Section: Introductionmentioning
confidence: 99%